Pengaruh Co-Firing Biomassa terhadap Efisiensi Boiler PLTU Batubara - Agus Noor Sidiq (Sekolah Tinggi Teknik - PLN, 2022)
The use of fossil fuels such as coal still dominates as fuel for power plants in the world. The use of fossil fuels in most power plants can increase Greenhouse Gas (GHG) emissions that affect climate change. Biomass is one of the renewable energy sources that is expected to reduce Greenhouse Gas emissions. The use of biomass energy sources as a mixture of fossil fuels known as co-firing in power plants has been widely done to reduce dependence on fossil fuels. In this research will be reviewed the influence of biomass mixture on the efficiency of coal power plant boilers. The composition of the mixture as well as the type of biomass used will greatly affect the efficiency of the Boiler. The percentage of biomass composition as well as the right combustion settings will be able to produce optimal boiler efficiency. From the study in this research, it is hoped that it will be able to provide an overview of the performance of a power plant that performs co-firing so that in addition to getting the benefits of reducing greenhouse gas emissions, good boiler efficiency is also obtained.